Astra Brata sebagai Role Model dalam Menjawab Krisis Kepemimpinan di Indonesia - Abdul Rochim, Syarif (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
This study aims to comprehensively explore the teachings of Astra Brata and analyze the relevance of its values as a leadership model within the context of Indonesia's leadership crisis. Employing a qualitative approach through library research, this study examines classical texts such as Serat Rama, Serat Nitisruti, and Serat Sruti Jarwa, alongside modern interpretations of ethics and leadership. This approach enables the identification of the core principles of Astra Brata, including justice, wisdom, integrity, and simplicity, which are deemed relevant in addressing contemporary challenges such as low public trust, corruption, and weak accountability. The findings reveal that the teachings of Astra Brata emphasize not only the physical aspects of leadership but also values such as justice, wisdom, integrity, and simplicity. For instance, Surya Brata underscores the importance of deliberation and justice in resolving social conflicts, while Bayu Brata highlights the need for vigilance and wisdom in understanding public aspirations. Meanwhile, Kuwera Brata emphasizes integrity and simplicity in addressing the growing social disparities in Indonesia. This study concludes that the teachings of Astra Brata offer a relevant and flexible normative framework for addressing Indonesia's leadership crisis, particularly within the complex social, political, and economic challenges of the modern era. By emphasizing ethical and moral aspects, these teachings provide sustainable solutions for creating leadership that is more inclusive, just, and oriented toward collective welfare.